2020
DOI: 10.18632/oncotarget.27663
|View full text |Cite
|
Sign up to set email alerts
|

TAF15 contributes to the radiation-inducible stress response in cancer

Abstract: Resistance to radiation therapy is a significant problem in the treatment of nonsmall cell lung cancer (NSCLC). There is an unmet need to discover new molecular targets for drug development in combination with standard of care cancer therapy. We found that TAF15 was radiation-inducible using phage-displayed peptide libraries. In this study, we report that overexpression of TAF15 is correlated with worsened survival in NSCLC patients. Radiation treatment led to surface induction of TAF15 in vitro and in vivo. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…TAF15 overexpression is associated with poor prognosis in patients NSCLC patients. 371 Aberrant gene transcription through loci-specific phase separation, which contribute to oncogenic transformation ability in relevant cancers. 372 P-TEFb 7SK snRNP complex, super elongation complex (SEC) Nucleus 1.…”
Section: Introductionmentioning
confidence: 99%
“…TAF15 overexpression is associated with poor prognosis in patients NSCLC patients. 371 Aberrant gene transcription through loci-specific phase separation, which contribute to oncogenic transformation ability in relevant cancers. 372 P-TEFb 7SK snRNP complex, super elongation complex (SEC) Nucleus 1.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of RBPs can cause changes to the expression of cancer‐related genes, leading to aberrant biological behaviors (Helder et al, 2016). TATA‐box binding protein associated factor 15 (TAF15) is a member of the FET family and exerts an important role in affecting messenger RNA (mRNA) stability, RNA splicing, and transportation (Singh et al, 2020). In our study, the correlation between BVES‐AS1 and TAF15 in COAD was tested.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have described that TAF15 is also involved in the cellular stress response, cell spreading and cell adhesion 10 , 28 , which are well known to play a crucial role in tumour cell migration and invasion 29 . Moreover, studies have revealed that TAF15 is associated with the processes of various of malignant tumours including non-small cell lung cancer and melanoma 8 , 13 . Nevertheless, not much is known about TAF15 in GC.…”
Section: Discussionmentioning
confidence: 99%
“…FET proteins are mainly present in the cell nucleus 10 , however, they are also present in the cell surface and cytoplasm 11 , 12 . Therefore, they have an extended function, including regulation and interaction with a number of various proteins 9 , 13 15 . FUS (fused in sarcoma/translocated in liposarcoma, FUS/TLS), a member of the FET family, can interact with lncRNA-MIR137HG and ultimately promote GC progression 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation